Early Surgery Is Feasible for a Very Large Congenital Infantile Fibrosarcoma Associated With Life Threatening Coagulopathy: A Case Report and Literature Review - Hamidah Alias; Hamidah Alias; Abdul Halim Abdul Rashid; Sie Chong Doris Lau; C-Khai Loh; Jamari Sapuan; Sharaf Ibrahim; Reena R. Md Zin; Yock Ping Chow; Hirokazu Kanegane; Mariko Eguchi (Frontiers Media S.A., 2019)
Background: Congenital infantile fibrosarcoma (CIF) is a rare malignant soft tissue tumor that predominantly occurs in children under 1 year of age. CIF is frequently misdiagnosed with other conditions like hemangioma of infancy, infantile fibromatosis, or kaposiform hemangioendothelioma. Disseminated intravascular coagulopathy (DIVC) is rarely reported to be associated with CIF.Case presentation: We describe an infant who presented with a large mass over the right arm. She was initially treated conservatively as hemangioma but was later confirmed by tissue histopathological examination to have CIF as the mass rapidly increased in size. She developed massive intra-tumoral bleed with DIVC whilst receiving neoadjuvant chemotherapy requiring multiple blood products transfusion. An urgent near-total resection of the tumor was performed in view of life threatening bleeding despite multiple blood transfusions. Post-operatively, she received further adjuvant chemotherapy. Subsequently, she remained in complete remission 32 months off-treatment and has full function of the affected limb.Conclusions: CIF is an important condition to be considered in infant who has large mass over the extremity. DIVC could be associated with large CIF and when it occurs can be life-threatening. Whenever feasible early surgery should be performed in very young patients with large CIF to prevent mortality from bleeding.